Penggunaan Instrumen Musik Taganing dan Keyboard dalam Iringan Nyanyian Ibadah Minggu di HKBP Palmarum Tarutung - Robert Simangunsong (Institut Agama Kristen Negeri Manado, 2022)
This study aims to determine the use of traditional Toba Batak taganing music instruments in collaboration with modern Western keyboards/music instruments to the accompaniment of Sunday worship songs at the HKBP Palmarum Tarutung church in 2015. The research method uses a descriptive method which aims to describe the use of taganing and keyboard musical instruments to accompany the music. Sunday worship songs at the HKBP Palmarum Tarutung church. Based on the results of this study, suggestions are made for the congregation and parhalado (management) of the HKBP Palmarum Tarutung church to look for taganing players who can then explain the technique of playing the instrument in accompanying Sunday worship songs so that the hitting technique is more varied, as well as conducting comparative studies with the Gondang music studio and the University Medan State University, North Sumatra University and HKBP Nommensen University Medan. For other researchers, this invention can be used as a reference for research on the use of taganing musical instruments and keyboards to accompany Sunday worship songs.